Psychosynthesis in Positive Psychotherapy - Zlatoslav Arabadzhiev; Stefanka Tomcheva (The Global Psychotherapist)
This article examines the integration of psychosynthesis and positive psychotherapy as a holistic therapeutic approach. Psychosynthesis, developed by Roberto Assagioli, emphasizes integrating conscious and unconscious aspects of personality to foster personal growth and spiritual fulfillment. Positive psychotherapy, introduced by Nossrat Peseschkian, focuses on activating individual resources to address psychological challenges through a structured, transcultural framework.